Public reason and multi-layered justice. (2nd January 2017) - Crum, Ben
ABSTRACT: This paper aims to outline a multi-layered conception of justice that is appropriate to the circumstances of justice in the European Union. Adopting the Rawlsian concept of public reason, it submits that duties of justice can only be imposed to the extent that the actors involved command a shared set of reasons by which these can be justified. The paper's argument follows Rawls in using public reason to justify a qualitative distinction between the demands that derive from the domestic and the international domain of justice. It criticises Rawls, however, for misjudging the radical implications of this position in a world that has become much more internationalised than he recognised it to be.